The Effect of Communication and Commitment on Employee Performance in the Department of Education, Youth and Sports - Nurhaida; Lindanur Sipatu; Rosida Adam; Andi Indriani Ibrahim; Wisra (Journal of Educational Management Research, 2026)
This study aims to examine the effect of communication and commitment on employee performance. A quantitative approach with a saturated sampling technique was employed, involving 60 employees as respondents. Data were collected using a validated and reliable questionnaire and analyzed using multiple linear regression. The results indicate that communication and commitment simultaneously have a significant effect on employee performance. Individually, both communication and commitment also show a significant positive effect. The coefficient of determination (R²) obtained is 0.825, indicating that 82.5% of the variance in employee performance is explained by communication and commitment, while the remaining 17.5% is influenced by other factors such as motivation, ability, and work environment. These findings suggest that enhancing communication and strengthening employee commitment are critical strategies for improving overall employee performance. Organizations should prioritize effective communication channels and initiatives that foster employee dedication and engagement.